Partisipasi Masyarakat Desa Waringin Kurung Terhadap Perkembangan Program Agroforestri - Indi Rahmawati; Fatihah Nurul Hayati; Andini Hania Pratiwi; Nabilla Putri Wahyuni; Shabrina Aulia Septiani; Annisa Hutami; Hidayatullah Haila (Eastasouth Journal of Effective Community Services, 2022)
Agroforestry is a program that provides several alternative land uses to support the development of forestry plants in order to increase the standard of living for the community by managing various agricultural crops as food and economic added value. Agroforestry systems provide important economic and ecological benefits for farmers, one of which can provide income for farmers. This study aims to identify forms of community empowerment, namely training in agroforestic programs. This research was conducted in Ssahan Village, Waringinkurung, Serang Regency, Banten. This research was carried out in October - November 2022 at the NGO Office of Ssahan Village, WaringinKurung, Serang Banten Regency. The data collection used is observation and interviews, by going directly to the field. The respondents were village officials. Research was conducted on the efforts made by village officials and related agencies so that they can empower village communities through gardens owned by village people, while there are beneficial results for villagers because they get additional income from the agroforestry program. So the researchers provide advice for village communities to take part in this empowerment training program in a systematic manner which the community will benefit from, while suggestions for village officials to continue to assist and monitor the progress of this agroforestry training.